Successful pregnancy in ovariectomized mice using a combination of heterotopic autotransplantation of ovarian tissues and embryo transfer - MITSUI, AKINORI (Reprod Med Biol, 2007)
Aim:  The present report is the first to show that, after ovariectomy, female mice with autotransplanted ovarian sections can maintain pregnancy after embryo transfer (ET) independent of the transplantation site. Methods:  Three‐month‐old ICR females were ovariectomized, and sections from their own ovaries were transplanted either under their kidney capsule (KC group) or into a subcutaneous space (SC group) just after ovariectomy. In vitro fertilized blastocysts were transferred into uterine horns of the pseudopregnant mice that had received the transplanted ovarian tissues. Cesarean sections were carried out 17 days after ET to deliver any live fetuses that were present, and the numbers of implantation sites and fetuses were noted. Transplanted ovarian sections were removed and fixed for histological analysis. Results:  Of the 10 mice in the KC group that received 107 blastocysts, two females (20%) became pregnant; they showed 12 implantation sites (11.2%) and produced four pups (3.7%). In the SC group, 101 blastocysts were transferred to eight females, and three females (37.5%) became pregnant; there were seven implantation sites (6.9%), and three pups (3.0%) were born. There were no statistically significant differences between the two groups in any of the parameters evaluated. On histological examination, luteinization and vascularization of the ovarian sections that were transplanted in the pregnant SC and KC females were noted. Conclusion:  The pregnancy and full‐term fetal development were obtained in ovariectomized mice using a combination of heterotopic ovarian tissue autotransplantation and transfer of embryos produced by in vitro fertilization.